The Feasibility of Guided Inquiry-Based Science Modules to Improve Student Product and Process Learning Outcomes on State of Matter Topic - Siti Aminah; Rahmat Yunus; Suyidno Suyidno (Universitas Muhammadiyah Sidoarjo, 2021)
Inquiry is the heart of science learning, but the process is rarely trained in elementary school students. Therefore, the purpose of this research is to produce a guided inquiry-based science module that is feasible to improve student learning outcomes of products and processes on the state of matter topic. This study uses education design research with the Tessmer model. However, this study was limited to the field test stage using a one-group pre-test and post-test design. The test subjects were 30 students of class V MIS Rumbai Kapuas. The research data was obtained through the instrument of observing student activities and product-process tests. The results showed that students were able to carry out inquiry activities at each meeting well. In addition, the students' product and process n-gains were 0.48 and 0.38, respectively, with moderate criteria. Thus, the guided inquiry-based science module is feasible to improve student learning outcomes of products and processes in science learning.